Peripheral delivery of neural precursor cells ameliorates parkinson’s disease-associated pathology - Edwards, George; Gámez, Nazaret; Armijo, Enrique; Kramm, Carlos; Morales, Rodrigo; Taylor-Presse, Kaithlyn; Schulz, Paul; Soto, Claudio; Moreno-González, Inés (MDPI, 2019)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by loss of motor control due to a wide loss of dopaminergic neurons along the nigro-striatal pathway. Some of the mechanisms that contribute to this cell death are inflammation, oxidative stress, and misfolded alpha-synuclein-induced toxicity. Current treatments are effective at managing the early motor symptoms of the disease, but they become ineffective over time and lead to adverse effects. Previous research using intracerebral stem cell therapy for treatment of PD has provided promising results; however, this method is very invasive and is often associated with unacceptable side effects. In this study, we used an MPTP-injected mouse model of PD and intravenously administered neural precursors (NPs) obtained from mouse embryonic and mesenchymal stem cells. Clinical signs and neuropathology were assessed. Female mice treated with NPs had improved motor function and reduction in the neuroinflammatory response. In terms of safety, there were no tumorigenic formations or any detectable adverse effect after treatment. Our results suggest that peripheral administration of stem cell-derived NPs may be a promising and safe therapy for the recovery of impaired motor function and amelioration of brain pathology in PD.
Keywords: Parkinson, Enfermedad de; Parkinson